MEDU-27. ENHANCING SELUMETINIB-MEDIATED KILLING OF SHH MEDULLOBLASTOMA. (23rd April 2019) - Guppy, Brent; Liang, Lisa; Cheng, Stephen; Porter, Christopher; Werbowetski-Ogilvie, Tamra
Abstract: Medulloblastoma (MB) is the most common primary malignant pediatric brain cancer with at least 5 distinct molecular subgroups. Of these subgroups, Sonic Hedgehog (SHH) MB exhibits extensive cellular heterogeneity, increased SHH signaling, and has an intermediate prognosis. Consequently, improved chemotherapeutic strategies designed to better treat SHH MB are needed. A major contributing factor to cellular heterogeneity, and thus drug resistance and disease progression, are rare putative brain tumor-propagating cells (TPC). We recently identified the neurotrophin receptor (CD271) within the SHH MB subgroup as a biomarker delineating TPC populations and associated with elevated MEK/ERK signaling. Moreover, we showed that selumetinib, a MEK inhibitor, reduced CD271 levels, decreased TPC growth, and extended survival in mouse models. While promising, these mice ultimately succumb to disease progression; thus, an enhanced selumetinib-based chemotherapeutic strategy is merited. Here, we employed RNA-sequencing to identify 543 genes differentially expressed in selumetinib resistant xenografts. Further, gene set enrichment analysis revealed significant changes in certain signaling pathways including JAK/STAT, predicted to underlie selumetinib resistance. Thus, we employed selumetinib in combination with the JAK/STAT inhibitors AZD1480 or pacritinib, to assess tumorsphere size and calculate drug synergy within human SHH MB cells. Following single agent IC50 studies, drug combinations were evaluated in our high-content tumorsphere assay. Preliminary results showed a synergistic reduction in tumorsphere size when combining selumetinib with JAK/STAT inhibition. We next evaluated cell migration and found that JAK/STAT inhibition alone was sufficient to produce a significant dose dependent reduction in migration. Interestingly, combinatorial drug treatment resulted in a synergistic reduction in cell migration, further supporting the use of selumetinib and JAK/STAT inhibitors as a potentially promising therapeutic combination. Our studies will reveal mechanisms of SHH MB drug resistance and identify novel drug combinations that may ultimately enhance MB patients' survival and quality of life.